Preparation method and application of self-healing and self-adhesive flexible conductive film
By combining natural cotton with conductive materials through chemical oxidation modification, a flexible conductive film that is healed, self-adhesive, green and environmentally friendly is prepared, which solves the problems of easy damage and lacks self-adhesion of the flexible conductive film, and realizes automatic healing and self-adhesion Viscous fusion, suitable for a variety of electronic devices, reduces maintenance costs and simplifies production processes.
Patent Information
- Application Number
- CN202411256832.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-06-06
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
AI Technical Summary
During use, existing flexible conductive films are prone to failure or reduced sensitivity due to scratches, wear, and rupture, and lack self-adhesion, which affects the actual application effect. Commonly used organic polymer materials have toxicity and environmental pollution problems. .
Natural cotton is combined with conductive materials through chemical oxidation modification to prepare a flexible conductive film that is healed, self-adhesive, green and environmentally friendly. The oxidation modification is carried out by a combination of oxidation reagents such as TEMPO, NaBr and NaClO to form modified cotton fibers The suspension is mixed with conductive materials and assembled into a film by vacuum suction filtration, natural drying or hot pressing, and has the characteristics of automatic healing and self-adhesiveness.
It realizes automatic healing and self-adhesive fusion with water wetting assistance, and can be assembled into complex shapes. It is suitable for flexible electronics, complex circuits and wearable devices, reduces maintenance costs, and is simple in process, low in cost, and is easy to mass production.
Smart Images

Figure CN119132738A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new materials, and specifically relates to a preparation method and application of a self-healing, self-adhesive flexible conductive film. Background Art
[0002] Conductive films are increasingly used in flexible electronics, wearable devices, near-field communication antennas and other fields. However, flexible electronic devices based on conductive films often suffer from scratches, wear, cracks, and aging during use, which can cause device failure or reduced sensitivity, shortening the service life of the device. To this end, researchers have begun to develop conductive films with self-healing functions from the material aspect. During use, when the self-healing conductive film is damaged by external stimuli, it can spontaneously or passively repair minor damage, so that the properties of the conductive film are restored to a state close to or reaching the original state, improving the durability of the conductive film, extending its service life, and reducing its maintenance cost. Most researchers use organic polymers with self-healing ability and conductive media to prepare self-healing conductive materials. However, these organic polymers generally have toxicity, are not environmentally friendly, are difficult to recycle, and cause environmental pollution. In addition, most conductive films lack self-adhesion, and additional tapes, adhesives, etc. are required to fix the conductive film on the surface of the substrate, which inevitably causes friction and affects the actual application effect. Therefore, it is of great significance to develop a flexible conductive film with self-healing, self-adhesive, and green environmental protection, which has become a technical problem that technicians in this field need to solve urgently. Summary of the invention
[0003] In view of the above problems, the present invention uses cotton as raw material, chemically oxidizes and modifies cotton, and compounds it with conductive materials to develop a self-healing, self-adhesive, green and environmentally friendly flexible conductive film. And using its self-healing and self-adhesive properties, a method for assembling conductive films into various complex shapes and integrating them with PVA, cellulose-based films, glass, paper, etc. has been developed. The self-healing, self-adhesive, green and environmentally friendly flexible conductive film developed by this patent has broad application prospects in the fields of flexible electronics, complex circuits, wearable devices, etc., and has important practical value.
[0004] The purpose of the present invention is to provide a method for preparing a self-healing, self-adhesive flexible conductive film, and the obtained self-healing, self-adhesive flexible conductive film product can be assembled into various complex shapes.
[0005] Another object of the present invention is to integrate the self-healing, self-adhesive flexible conductive film onto the surfaces of various substrates to prepare flexible device products.
[0006] The object of the present invention is achieved through the following solutions:
[0007] A method for preparing a self-healing, self-adhesive flexible conductive film, comprising the following steps:
[0008] (1) placing natural cotton in a solution containing an oxidizing agent for oxidation modification, and during the oxidation modification process, adjusting the pH value of the solution to between 8 and 11 by adding NaOH;
[0009] (2) further subjecting the cotton fibers oxidatively modified in step (1) to a mechanical shearing treatment in an aqueous solution to form a modified cotton fiber suspension;
[0010] (3) mixing the modified cotton fiber suspension obtained in step (2) with a conductive material dispersion;
[0011] (4) Assembling the mixed solution obtained in step (3) into a self-healing, self-adhesive flexible conductive film.
[0012] In step (1), the oxidizing agent is a combination of 2,2,6,6-tetramethylpyridine-1-oxyl radical (TEMPO), sodium bromide (NaBr), and sodium hypochlorite (NaClO); and the mass ratio of cotton, TEMPO, NaBr and NaClO is 12: (0.01-0.8): (0.5-5): (30-200).
[0013] Alternatively, the oxidizing agent is a combination of 2,2,6,6-tetramethylpyridine-1-oxyl radical (TEMPO), sodium bromide (NaBr) and sodium chlorite (NaClO2), and the mass ratio of cotton, TEMPO, NaBr and NaClO2 is 12: (0.01-0.8): (0.5-5): (50-300).
[0014] In step (3), after the modified cotton fiber suspension is mixed with the conductive material dispersion, the mass ratio of the modified cotton fiber to the conductive material is 1:(0.04-1.5).
[0015] The conductive material is Ag, Cu or Ni nanowires or nanoparticles, carbon material, or polypyrrole polymer material.
[0016] In step (4), the assembly method is vacuum filtration, natural drying, hot pressing or spin coating.
[0017] The present invention provides a self-healing, self-adhesive flexible conductive film product, which is prepared according to the above method and has self-healing and self-adhesive properties. Specifically, with the assistance of water wetting, the cut conductive film can automatically heal together; with the assistance of water wetting, the conductive films can be fused together after being stacked by relying on their self-adhesiveness; with the assistance of water wetting, the conductive film can maintain its state when bent and deformed, and after naturally drying, it can form various complex shapes, which can be used in the design of various complex circuits and electronic devices. The self-healing, self-adhesive flexible conductive film product of the present invention is used to prepare applications in flexible electronics, complex circuits or wearable devices. The specific steps are as follows:
[0018] (1) Wetting the substrate with water;
[0019] (2) placing a conductive film on the surface of the substrate;
[0020] (3) After natural drying, the conductive film is fused to the substrate.
[0021] The substrate includes cellulose film, polyvinyl alcohol (PVA), paper or glass.
[0022] The present invention has the following advantages and features:
[0023] (1) The preparation method of the present invention has the characteristics of simple process, low cost, and easy large-scale industrial production.
[0024] (2) The present invention uses natural plant fiber cotton as raw material, which is abundant and easy to obtain and belongs to natural plant fiber. The prepared flexible conductive film not only has self-healing properties, but also has the characteristics of self-adhesion and green environmental protection.
[0025] (3) The present invention utilizes the self-healing and self-adhesive properties of the conductive film. With the assistance of water wetting, the damaged conductive film can be simply and quickly repaired. It can also be assembled into various complex shapes and integrated with a variety of substrates for use in the fields of flexible electronics, complex circuits, wearable devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The following is a photograph showing the self-healing, self-adhesive flexible conductive film prepared in Example 1 and its self-healing ability.
[0027] Figure 2 This is a display diagram of Example 12, in which the prepared conductive film is assembled into various complex shapes.
[0028] Figure 3 This is a diagram showing how the conductive film prepared in Example 13 is fused onto different substrate surfaces.
[0029] Figure 4The following are diagrams showing the working of the fused conductive film / substrate as a flexible circuit in Example 14. (ac) Conductive film / cellulose film substrate; (df) Conductive film / PVA substrate; (gh) Conductive film / glass substrate; (il) The process of repairing a damaged circuit by using the self-adhesiveness of the conductive film. DETAILED DESCRIPTION
[0030] Example 1
[0031] Preparation of functionalized flexible transparent films using cotton:
[0032] Step 1) 12g of cotton is dispersed in 700ml of deionized water using a stirrer. Then, 20ml of 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 20ml of 10wt% NaBr aqueous solution are added to the cotton fiber suspension. After stirring evenly, 100g of NaClO is slowly added to the mixed solution. During this process, 3M NaOH is used to adjust the pH value of the solution to keep the pH value between 8 and 11. After the reaction is completed, the oxidatively modified cotton fiber is washed with deionized water.
[0033] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0034] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:0.2.
[0035] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0036] Example 2
[0037] Self-healing, self-adhesive flexible conductive films made from cotton and silver nanowires:
[0038] Step 1) Chemically oxidize and modify cotton by dispersing 12 g of cotton in 700 ml of deionized water using a stirrer. Then, add 80 ml of 1 wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 5 ml of 10 wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 30 g of NaClO to the mixed solution. During this process, 3 M NaOH is used to adjust the pH value of the solution to keep the pH value between 8 and 11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0039] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0040] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:0.04.
[0041] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0042] Example 3
[0043] Preparation of functionalized flexible transparent films using cotton:
[0044] Step 1) 12g of cotton is dispersed in 700ml of deionized water using a stirrer. Then, 20ml of 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 20ml of 10wt% NaBr aqueous solution are added to the cotton fiber suspension. After stirring evenly, 100g of NaClO is slowly added to the mixed solution. During this process, 3M NaOH is used to adjust the pH value of the solution to keep the pH value between 8 and 11. After the reaction is completed, the oxidatively modified cotton fiber is washed with deionized water.
[0045] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0046] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:0.11.
[0047] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0048] Example 4
[0049] Preparation of functionalized flexible transparent films using cotton:
[0050] Step 1) Disperse 12g cotton in 700ml deionized water with a stirrer. Then, add 10ml 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 50ml 10wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 200g NaClO to the mixed solution. During this process, use 3M NaOH to adjust the pH value of the solution to keep the pH value between 8-11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0051] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0052] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:0.2.
[0053] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0054] Example 5
[0055] Preparation of functionalized flexible transparent films using cotton:
[0056] Step 1) Disperse 12g cotton in 700ml deionized water with a stirrer. Then, add 5ml 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 70ml 10wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 250g NaClO to the mixed solution. During this process, use 3M NaOH to adjust the pH value of the solution to keep the pH value between 8-11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0057] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0058] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:0.5.
[0059] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0060] Example 6
[0061] Preparation of functionalized flexible transparent films using cotton:
[0062] Step 1) Disperse 12g cotton in 700ml deionized water with a stirrer. Then, add 3ml 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 80ml 10wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 300g NaClO to the mixed solution. During this process, use 3M NaOH to adjust the pH value of the solution to keep the pH value between 8-11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0063] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0064] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:1.0.
[0065] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0066] Example 7
[0067] Preparation of functionalized flexible transparent films using cotton:
[0068] Step 1) Disperse 12g cotton in 700ml deionized water with a stirrer. Then, add 3ml 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 90ml 10wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 300g NaClO to the mixed solution. During this process, use 3M NaOH to adjust the pH value of the solution to keep the pH value between 8-11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0069] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0070] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:1.5.
[0071] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0072] Example 8
[0073] Preparation of functionalized flexible transparent films using cotton:
[0074] Step 1) 12g of cotton is dispersed in 700ml of deionized water using a stirrer. Then, 80ml of 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 5ml of 10wt% NaBr aqueous solution are added to the cotton fiber suspension. After stirring evenly, 50g of NaClO2 is slowly added to the mixed solution. During this process, 3M NaOH is used to adjust the pH value of the solution to keep the pH value between 8 and 11. After the reaction is completed, the oxidized cotton fiber is washed with deionized water.
[0075] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0076] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:0.04.
[0077] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0078] Example 9
[0079] Preparation of functionalized flexible transparent films using cotton:
[0080] Step 1) 12g of cotton is dispersed in 700ml of deionized water using a stirrer. Then, 20ml of 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 20ml of 10wt% NaBr aqueous solution are added to the cotton fiber suspension. After stirring evenly, 100g of NaClO2 is slowly added to the mixed solution. During this process, 3M NaOH is used to adjust the pH value of the solution to keep the pH value between 8 and 11. After the reaction is completed, the oxidized cotton fiber is washed with deionized water.
[0081] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0082] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:0.2.
[0083] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0084] Example 10
[0085] Preparation of functionalized flexible transparent films using cotton:
[0086] Step 1) 12g of cotton is dispersed in 700ml of deionized water using a stirrer. Then, 10ml of 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 60ml of 10wt% NaBr aqueous solution are added to the cotton fiber suspension. After stirring evenly, 200g of NaClO2 is slowly added to the mixed solution. During this process, 3M NaOH is used to adjust the pH value of the solution to keep the pH value between 8 and 11. After the reaction is completed, the oxidatively modified cotton fiber is washed with deionized water.
[0087] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0088] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:0.5.
[0089] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0090] Embodiment 11
[0091] Preparation of functionalized flexible transparent films using cotton:
[0092] Step 1) Disperse 12g of cotton in 700ml of deionized water using a stirrer. Then, add 5ml of 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 70ml of 10wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 300g of NaClO2 to the mixed solution. During this process, use 3M NaOH to adjust the pH value of the solution to keep the pH value between 8 and 11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0093] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0094] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with the silver nanowire solution, and the ratio of the modified cotton mass to the silver nanowire mass is 1:1.0.
[0095] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0096] As an example, Figure 1 The self-healing, self-adhesive flexible conductive film prepared by cotton and silver nanowires in Example 1 is shown, which can be used as a conductor to light up an LED lamp. The conductive film is cut open, and the fracture is moistened with water. After drying, the fracture of the film will automatically heal together. When the conductive film after self-healing is bent and deformed, the fracture does not crack and is firmly connected. Figure 1 (a) is the self-healing, self-adhesive flexible conductive film prepared in Example 1; (b) the conductive film is cut; (c) the conductive film is moistened with water; (d) after drying, the fracture of the conductive film is automatically healed together; (e) in the case of bending deformation, the healed part of the conductive film is still firmly connected; (f) the healed conductive film is used as a wire to light up an LED lamp.
[0097] Example 12
[0098] The self-healing, self-adhesive flexible conductive film prepared in Example 1 is assembled into various complex shapes by utilizing the self-adhesiveness of the film: Step 1) The conductive films are stacked on top of each other or bent into various shapes;
[0099] Step 2) Wetting the conductive film with water;
[0100] Step 3) After natural drying, the contact parts of the conductive films fuse together or maintain a bent state to form a corresponding shape.
[0101] As an example, Figure 2 Demonstrated various complex shapes assembled from conductive films,
[0102] Example 13
[0103] By utilizing the self-adhesiveness of the film, the self-healing, self-adhesive flexible conductive film prepared in Example 1 is fused to the surface of various substrates: Step 1) the substrate is moistened with water (substrate: cellulose film, polyvinyl alcohol (PVA), paper, glass, etc. The substrates to which the conductive film can be fused include but are not limited to the above-mentioned substrates, and other fused substrates are also within the scope of protection of this patent);
[0104] Step 2) placing a conductive film on the substrate;
[0105] Step 3) After natural drying, the conductive film is fused to the substrate;
[0106] Figure 3 Examples of conductive films fused to the surfaces of different substrates are shown: (a) cellulose film substrate; (b) polyvinyl alcohol (PVA) substrate; (c) paper substrate; and (d) glass substrate.
[0107] Embodiment 14
[0108] To demonstrate the application of the conductive film prepared in Example 1 and fused with different substrates in the fields of flexible circuits, electronic devices, etc. The LED lamp can be glued to the conductive film / substrate with conductive silver glue to work as a flexible circuit. Figure 4 In the example, (a)-(c) show the conductive film / cellulose film substrate, (d)-(f) show the conductive film / PVA substrate, and (g)-(h) show the conductive film / glass substrate as an example of circuit operation. In addition, this example also shows that when the conductive circuit is damaged during use ( Figure 4 The i red box) uses the self-adhesiveness of the conductive film to repair the damaged circuit, that is, add water to moisten it, place the conductive film on the damaged part, and after it dries naturally, the damaged part is repaired and the conductive circuit works normally ( Figure 4 This patent includes but is not limited to the application of this conductive film in the field of flexible circuits. The application of this conductive film in other flexible circuits, electronic devices, wearable devices, antennas, the Internet of Things and other fields is also within the scope of protection of this patent.
[0109] Embodiment 15
[0110] Using cotton and other conductive materials (Cu or Ni nanowires or nanoparticles, or carbon materials, or polypyrrole polymer materials) to prepare self-healing, self-adhesive flexible conductive films:
[0111] Step 1) Chemically oxidize and modify cotton by dispersing 12 g of cotton in 700 ml of deionized water using a stirrer. Then, add 80 ml of 1 wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 5 ml of 10 wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 30 g of NaClO to the mixed solution. During this process, 3 M NaOH is used to adjust the pH value of the solution to keep the pH value between 8 and 11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0112] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0113] Step 3) The above-mentioned oxidized modified cotton fiber suspension is mixed with other conductive material (Cu or Ni nanowires or nanoparticles, or carbon materials, or polypyrrole polymer materials) solutions, and the ratio of the modified cotton mass to the conductive material mass is 1:0.04.
[0114] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0115] Example 16
[0116] Preparation of functionalized flexible transparent films using cotton:
[0117] Step 1) 12g of cotton is dispersed in 700ml of deionized water using a stirrer. Then, 20ml of 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 20ml of 10wt% NaBr aqueous solution are added to the cotton fiber suspension. After stirring evenly, 100g of NaClO is slowly added to the mixed solution. During this process, 3M NaOH is used to adjust the pH value of the solution to keep the pH value between 8 and 11. After the reaction is completed, the oxidatively modified cotton fiber is washed with deionized water.
[0118] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0119] Step 3) The above-mentioned oxidized modified cotton fiber suspension is mixed with other conductive material (Cu or Ni nanowires or nanoparticles, or carbon materials, or polypyrrole polymer materials) solutions, and the ratio of the modified cotton mass to the conductive material mass is 1:0.11.
[0120] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0121] Embodiment 17
[0122] Preparation of functionalized flexible transparent films using cotton:
[0123] Step 1) Disperse 12g cotton in 700ml deionized water with a stirrer. Then, add 10ml 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 50ml 10wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 200g NaClO to the mixed solution. During this process, use 3M NaOH to adjust the pH value of the solution to keep the pH value between 8-11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0124] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0125] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with other conductive material (Cu or Ni nanowires or nanoparticles, or carbon materials, or polypyrrole polymer materials) solutions, and the ratio of the modified cotton mass to the conductive material mass is 1:0.2.
[0126] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0127] Embodiment 18
[0128] Preparation of functionalized flexible transparent films using cotton:
[0129] Step 1) Disperse 12g cotton in 700ml deionized water with a stirrer. Then, add 5ml 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 70ml 10wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 250g NaClO to the mixed solution. During this process, use 3M NaOH to adjust the pH value of the solution to keep the pH value between 8-11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0130] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0131] Step 3) The above-mentioned oxidatively modified cotton fiber suspension is mixed with other conductive material (Cu or Ni nanowires or nanoparticles, or carbon materials, or polypyrrole polymer materials) solutions, and the ratio of the modified cotton mass to the conductive material mass is 1:0.5.
[0132] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0133] Embodiment 19
[0134] Preparation of functionalized flexible transparent films using cotton:
[0135] Step 1) Disperse 12g cotton in 700ml deionized water with a stirrer. Then, add 3ml 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 80ml 10wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 300g NaClO to the mixed solution. During this process, use 3M NaOH to adjust the pH value of the solution to keep the pH value between 8-11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0136] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0137] Step 3) The above-mentioned oxidized modified cotton fiber suspension is mixed with other conductive material (Cu or Ni nanowires or nanoparticles, or carbon materials, or polypyrrole polymer materials) solutions, and the ratio of the modified cotton mass to the conductive material mass is 1:1.0.
[0138] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then naturally dried in the air to prepare a self-healing, self-adhesive flexible conductive film.
[0139] Embodiment 20
[0140] Preparation of functionalized flexible transparent films using cotton:
[0141] Step 1) Disperse 12g cotton in 700ml deionized water with a stirrer. Then, add 3ml 1wt% 2,2,6,6-tetramethylpiperidin-1-oxyl (TEMPO) aqueous solution and 90ml 10wt% NaBr aqueous solution to the cotton fiber suspension. After stirring evenly, slowly add 300g NaClO to the mixed solution. During this process, use 3M NaOH to adjust the pH value of the solution to keep the pH value between 8-11. After the reaction is completed, wash the oxidatively modified cotton fiber with deionized water.
[0142] Step 2) putting the washed oxidized modified cotton fiber into a wall breaking machine, adding deionized water, and then performing mechanical shearing treatment to form an oxidized modified cotton fiber suspension.
[0143] Step 3) The above-mentioned oxidized modified cotton fiber suspension is mixed with other conductive material (Cu or Ni nanowires or nanoparticles, or carbon materials, or polypyrrole polymer materials) solutions, and the ratio of the modified cotton mass to the conductive material mass is 1:1.5.
[0144] Step 4) The mixed solution is densified and assembled by vacuum filtration, and then dried naturally in the air to prepare a self-healing, self-adhesive flexible conductive film. This patent includes but is not limited to the application of this conductive film in the field of flexible circuits. The application of this conductive film in other flexible circuits, electronic devices, wearable devices, antennas, the Internet of Things and other fields is also within the scope of protection of this patent.
Claims
1. A method for preparing a self-healing, self-adhesive flexible conductive film, It is characterized in that The steps include: (1) placing natural cotton in a solution containing an oxidizing agent for oxidation modification, and during the oxidation modification process, adjusting the pH value of the solution to between 8 and 11 by adding NaOH; (2) further subjecting the cotton fibers oxidatively modified in step (1) to a mechanical shearing treatment in an aqueous solution to form a modified cotton fiber suspension; (3) mixing the modified cotton fiber suspension obtained in step (2) with a conductive material dispersion; (4) Assembling the mixed solution obtained in step (3) into a self-healing, self-adhesive flexible conductive film.
2. The preparation method according to claim 1, It is characterized in that In step (1), the oxidizing agent is a combination of 2,2,6,6-tetramethylpyridine-1-oxyl free radical TEMPO, sodium bromide NaBr, and sodium hypochlorite NaClO; and the mass ratio of cotton, TEMPO, NaBr and NaClO is 12: (0.01-0.8): (0.5-5): (30-200).
3. The preparation method according to claim 1, It is characterized in that In step (1), the oxidizing agent is 2,2,6,6-tetramethylpyridine-1-oxyl free radical TEMPO, sodium bromide NaBr and sodium chlorite NaClO 2 Combination of cotton, TEMPO, NaBr and NaClO 2 The mass ratio is 12: (0.01~0.8): (0.5~5): (50~300).
4. The preparation method according to claim 1, It is characterized in that In step (3), after the modified cotton fiber suspension is mixed with the conductive material dispersion, the mass ratio of the modified cotton fiber to the conductive material is 1:(0.04-1.5).
5. The preparation method according to claim 1, It is characterized in that In step (3), the conductive material is Ag, Cu or Ni nanowires or nanoparticles, carbon materials, or polypyrrole polymer materials.
6. The preparation method according to claim 1, It is characterized in that In step (4), the assembly method is vacuum filtration, natural drying, hot pressing or spin coating.
7. A self-healing, self-adhesive flexible conductive film, It is characterized in that It is prepared by the preparation method described in any one of claims 1 to 6, and has self-healing and self-adhesive properties, which are manifested in that: with the assistance of water wetting, the conductive films can be fused together by relying on their self-adhesiveness after being stacked, or maintain the state of bending and deformation, and form various complex shapes after natural drying.
8. Use of the self-healing, self-adhesive flexible conductive film according to claim 7 in preparing flexible electronics, complex circuits or wearable devices.
9. The use according to claim 8, It is characterized in that The steps are: (1) Wetting the substrate with water; (2) placing a conductive film on the surface of the substrate; (3) After natural drying, the conductive film is fused to the substrate.
10. The use according to claim 9, It is characterized in that The substrate includes cellulose film, polyvinyl alcohol (PVA), paper or glass.
